PERUBAHAN WARNA DAN ORGANOLEPTIK BUAH MANGGA GOLEK (Mangifera indica L.) PADA METODE PENYIMPANAN ZERO ENERGY COOL CHAMBER (ZECC) DENGAN KOMBINASI PENGEMASAN - Andi Dirpan; Andi Nurfaidah Rahman; Muhammad Tahir Sapsal; Mulyati M. Tahir; Singgang Dewitara (Jurnal Agritechno, 2021)
The increase in the amount of mango fruit production is due to their high nutritional content affordable, and relatively easy to find. However, like other horticultural crops, Mango can be easily bruised or damaged. The fruit damage can be caused by improper post-harvest handling, causing mango quality and has a short shelf life. The study aimed to determine the shelf life and quality of mango Golek stored in Zero Energy Cool Chamber (ZECC) using LDPE packaging and LDPE packaging with additional perforations. The first stage was observing the physical quality of the fruit and then post-harvest treatment such as washing, packaging and storing mangoes at ZECC temperature (±26°C). The second stage was the mango quality test after storage. Tests in the form of skin color and organoleptic. The results obtained in this study were mangoes packed with LDPE and LDPE with perforations. Mango packaged in LDPE packaging were able to retain L* color, b* color, organoleptic color, aroma, texture and taste. Mangoes packed with perforated LDPE packaging can retail, L * color, b * color, organoleptic color, aroma, texture and taste